H-IPSE is a pathogen-secreted host nucleus infiltrating protein (infiltrin) expressed exclusively by the Schistosoma haematobium egg stage - Pennington, Luke F.; Alouffi, Abdulaziz; Mbanefo, Evaristus C.; Ray, Debalina; Heery, David M.; Jardetzky, Theodore S.; Hsieh, Michael H.; Falcone, Franco H. (ASM Press, 2017)
Urogenital schistosomiasis, caused by the parasitic trematode Schistosoma haematobium, affects over 112 million people worldwide. As with S. mansoni infections, the pathology in urogenital schistosomiasis is mainly related to the egg stage, which induces granulomatous inflammation of affected tissues. Schistosoma eggs and their secretions have been studied extensively for the related S. mansoni organism which is more amenable to laboratory studies. Indeed, we have shown that IPSE/alpha-1 (M-IPSE herein), a major protein secreted from S .mansoni eggs, can infiltrate host cells. Although M-IPSE function is unknown, its ability to translocate to their nucleus and bind DNA suggests a possible role in immune modulation of host cell tissues. Whether IPSE homologs are expressed in other Schistosome species has not been investigated.